1997
DOI: 10.1097/00000539-199705000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental-Rocuronium Versus Ketamine-Rocuronium for Rapid-Sequence Intubation in Parturients Undergoing Cesarean Section

Abstract: We investigated the neuromuscular effects and conditions of tracheal intubation after administration of rocuronium in 40 parturients undergoing elective cesarean section. After preoxygenation, anesthesia was induced in 20 patients by thiopental 4 mg/kg and, in the other 20 patients, by ketamine 1.5 mg/kg. Rocuronium 0.6 mg/kg was then administered, and neuromuscular transmission was assessed using electromyographic response to train-of-four stimulation of the ulnar nerve at the wrist every 10 s. The time to T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…Hence intravenous anaesthetic agents with the shortest t 1 ⁄ 2 K eo are generally best suited to the non-titrated use in RSI (Table 1). Consistent with this notion, a study using ketamine 1.5 mg.kg )1 vs thiopentone 4 mg.kg )1 in obstetric practice (RSI with rocuronium 0.6 mg.kg )1 ) reported satisfactory conditions for early intubation (45 s) in all cases in ketamine, while thiopentone caused difficulty in 75% of cases [5].…”
Section: Pharmacokinetics and Pharmacodynamics In Shocked Patientsmentioning
confidence: 65%
“…Hence intravenous anaesthetic agents with the shortest t 1 ⁄ 2 K eo are generally best suited to the non-titrated use in RSI (Table 1). Consistent with this notion, a study using ketamine 1.5 mg.kg )1 vs thiopentone 4 mg.kg )1 in obstetric practice (RSI with rocuronium 0.6 mg.kg )1 ) reported satisfactory conditions for early intubation (45 s) in all cases in ketamine, while thiopentone caused difficulty in 75% of cases [5].…”
Section: Pharmacokinetics and Pharmacodynamics In Shocked Patientsmentioning
confidence: 65%
“…In the present study, the two groups differed only in the induction agent. In a study comparing thiopentone-rocuronium with ketamine-rocuronium for rapid sequence intubation in parturients undergoing Caesarean section, intubating conditions at 50% neuromuscular block of the adductor pollicis were significantly better after ketamine than after thiopentone [14]. In that study, neither the time to 50% neuromuscular block nor the onset time were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 87%
“…Baraka et al and Hans et al showed that ketamine provided better intubation conditions than thiopental. 20,21 However, the ketamine doses used in these studies were 1.5 mg kg -1 and 2.5 mg kg -1 , respectively. Ledowski and Wulf 22 found that the intubation conditions of 0.6 mg.kg -1 rocuronium were better in ketamine-etomidate induction group; however, arterial blood pressure and heart rate were also higher in this group.…”
Section: Discussionmentioning
confidence: 99%